Cotton fabric with plasma pretreatment and ZnO/Carboxymethyl chitosan composite finishing for durable UV resistance and antibacterial property. (15th March 2016) - Wang, Chunxia; Lv, Jingchun; Ren, Yu; Zhou, Qingqing; Chen, Jiayi; Zhi, Tian; Lu, Zhenqian; Gao, Dawei; Ma, Zhipeng; Jin, Limin
Highlights: A new method of cotton fabric finishing with plasma pretreatment and ZnO/CMCS composite for durable functions. UV resistance and antibacterial activity of the finished cotton fabric were significantly increased. Plasma modification had a positive effect on loading efficiency of ZnO/CMCS and property improvement. The finished cotton fabric exhibited an excellent laundering durability in UV resistance and antibacterial activity. Abstract: ZnO/carboxymethyl chitosan (ZnO/CMCS) composite was prepared and confirmed by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Ultraviolet–visible (UV–vis) spectroscopy, Scanning electron microscope (SEM), Transmission electron microscope (TEM). The combination of plasma pretreatment and ZnO/CMCS composite finishing was applied to provide durable UV resistance and antibacterial activity for cotton fabric. Cotton fabric was pretreated by cold oxygen plasma and the ZnO/CMCS composite finishing was carried out by pad-dry-cure. Cotton fabric was characterized by SEM, FTIR, UV resistance, antibacterial activity and Thermogravimetry (TG). SEM and FTIR analysis demonstrated the presence of ZnO/CMCS composite on cotton fabric and the increasing loading efficiency of ZnO/CMCS composite owing to plasma treatment. UV resistance and antibacterial activity of the finished cotton fabric were greatly improved, which increased with the increasing concentration of ZnO/CMCS composite. TG analysis indicated that the combined finishing of cotton fabric with plasma pretreatment and ZnO/CMCS composite could improve its thermal property. The finished cotton fabric exhibited an excellent laundering durability in UV resistance and antibacterial activity.